PKM PENTINGNYA AKUNTABILITAS, SOCIAL ENTERPRISE DAN SOSIAL BUDAYA DALAM PEMBERDAYAAN MASYARAKAT DESA - Anastasia Yelisa Simon (Jurnal Abdimas Bina Bangsa, 2023)
This research is Interpretivism  research with the aim of finding explanations about existing social events or culture based on perspectives and experiences in one of the villages in Buton. This research uses a qualitative approach with basic research methods. The data obtained are from the condition of accountability, social enterprise and socio-culture in one of the villages in Buton. The results showed that there was no audit related to the village fund report and was supported by the results of interviews. In addition, BUMDes are business entities that are not only looking for profit but also for social activities in the village such as helping villagers if there is a disaster. In practice, this accountability can make the village apparatus more open in terms of reporting and is supported by a culture of honest, transparent and responsible village apparatus so that accountability is not solely about making a report but also absorbing the aspirations of the community until consensus is reached. The results of other studies show that the quality of human resources of the village apparatus has sufficient good knowledge in terms of village operational activities and has high loyalty. In addition, making village reports is supported by government policies around the village through guidebooks to implement the allocation of village funds